The REC2 gene encodes the homologous pairing protein of Ustilago maydis. - Kmiec, E B (1994)
Amino acid sequence analysis has established that the homologous pairing protein of Ustilago maydis, known previously in the literature as rec1, is encoded by REC2, a gene essential for recombinational repair and meiosis with regional homology to Escherichia coli RecA. The 70-kDa rec1 protein is most likely a proteolytic degradation product of REC2, which has a predicted mass of 84 kDa but which runs anomalously during sodium dodecyl sulfate-gel electrophoresis with an apparent mass of 110 kDa. To facilitate purification of the protein product, the REC2 gene was overexpressed from a vector that fused a hexahistidine leader sequence onto the amino terminus, enabling isolation of the REC2 protein on an immobilized metal affinity column. The purified protein exhibits ATP-dependent DNA renaturation and DNA-dependent ATPase activities, which were reactions characteristic of the protein as purified from cell extracts of U. maydis. Homologous pairing activity was established in an assay that measures recognition via non-Watson-Crick bonds between identical DNA strands. A size threshold of about 50 bp was found to govern pairing between linear duplex molecules and homologous single-stranded circles. Joint molecule formation with duplex DNA well under the size threshold was efficiently catalyzed when one strand of the duplex was composed of RNA. Linear duplex molecules with hairpin caps also formed joint molecules when as few as three RNA residues were present.